Vitamin D and immunomodulation in the skin: a useful affirmative nexus - Saptadip Samanta (Open Exploration Publishing Inc., 2021)
Skin is the largest organ of the body having multifunctional activities. It has a dynamic cellular network with unique immunologic properties to maintain defensive actions, photoprotection, immune response, inflammation, tolerogenic capacity, wound healing, etc. The immune cells of the skin exhibit distinct properties. They can synthesize active vitamin D [1,24(OH)2D3] and express vitamin D receptors. Any difficulties in the cutaneous immune system cause skin diseases (psoriasis, vitiligo, atopic dermatitis, skin carcinoma, and others). Vitamin D is an essential factor, exhibits immunomodulatory effects by regulating dendritic cells’ maturation, lymphocytes’ functions, and cytokine production. More specifically, vitamin D acts as an immune balancing agent, inhibits the exaggeration of immunostimulation. This vitamin suppresses T-helper 1 and T-helper 17 cell formation decreases inflammatory cytokines release and promotes the maturation of regulatory T cells and interleukin 10 secretion. The deficiency of this vitamin promotes the occurrence of immunoreactive disorders. Administration of vitamin D or its analogs is the therapeutic choice for the treatment of several skin diseases.